Perlindungan Hukum Investor Publik dalam Praktik Perdagangan Orang dalam di Indonesia - Endang Sholehin; Retno Wulansari (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to find out about how the form of legal protection for public investors against insider trading cases and to find out how the efforts made by the OJK or other institutions in handling insider trading cases. This type of research is normative legal research. The approach method used is a legal approach or approach based on legislation. The data sources obtained consist of secondary data sources through primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study are first, In the Insider Trading case committed by Rajiv Louis, it fulfills all the elements of Insider Trading regulated in Article 95 of Law Number 8 of 1995. The form of protection or law enforcement in regulating insider trading includes three things, namely civil, criminal and administrative enforcement. The capital market law itself has provided a basis for law enforcement as a protection effort for any violations in capital market activities, namely the existence of administrative sanctions (Article 102 of the capital market law), criminal sanctions (Article 110 of the capital market law), civil sanctions (Article 111 of the capital market law). The form of legal protection itself can be in the form of legal structure and legal substance, both of which are interconnected to provide legal certainty and protection. Second, the role of OJK in this case